Analytical methods assessment for exchangeable cations analysis in soil: MIP OES appraisement - Jofré, Florencia Cora (2020)
Soil monitoring and research often requires a comparison of laboratory data generated by diverse instruments and in different laboratories to demonstrate the reliability and accuracy of the results. The outcomes of this work highlight a performance comparison among different analytical methods for the determination of calcium (Ca), magnesium (Mg), sodium (Na), and potassium (K), in soil. Five soil samples were used for analytical methods comparison, corresponding to an argentine agricultural soil interlaboratory, and four soil samples from the Pampa region of Argentina were used for analytical application of the instrumental methods. The results obtained with flame atomic absorption and emission spectrometry (FAAS-FAES) and microwaveinduced plasma optical emission spectrometry (MIP OES) were compared to those obtained by conventional analytical methods as complexometric titration and flame photometry. As there were no significant differences between classical methods with instrumental ones, FAAS-FAES and MIP OES were validated following criteria based on international guidelines. Accuracy, precision, linearity, limits of detection and quantification, sensitivity, analytical sensitivity, and working range were evaluated. The results established the satisfactory performance of FAAS-FAES and MIP OES for exchangeable cations. MIP OES is an efficient alternative to FAAS FAES, with wide linear dynamic range, which is advantageous concerning to the concentrations in which these exchangeable cations are found in soils, avoiding sample dilutions. The most remarkable advantage of MIP OES is the low running costs as it does not use flammable and toxic gases. Due to its benefits MIP OES could be recommended as the main analytical method for exchangeable cations determination. El monitoreo y la investigación del suelo a menudo requieren una comparación de datos de laboratorio generados por diversos instrumentos y en diferentes laboratorios para demostrar la confiabilidad y precisión de los resultados. Los resultados de este trabajo destacan una comparación de desempeño entre diferentes métodos analíticos para la determinación de calcio (Ca), magnesio (Mg), sodio (Na) y potasio (K), en suelo. Se utilizaron cinco muestras de suelo para la comparación de métodos analíticos, correspondientes a un interlaboratorio de suelos agrícolas argentinos, y cuatro muestras de suelo de la región pampeana de Argentina para la aplicación analítica de los métodos instrumentales. Los resultados obtenidos con la espectrometría de emisión y absorción atómica de llama (FAAS-FAES) y la espectrometría de emisión óptica de plasma inducida por microondas (MIP OES) se compararon con los obtenidos por métodos analíticos convencionales como titulación complexométrica y fotometría de llama. Al no existir diferencias significativas entre los métodos clásicos y los instrumentales, se validaron FAAS-FAES y MIP OES siguiendo criterios basados ​​en guías internacionales. Se evaluaron exactitud, precisión, linealidad, límites de detección y cuantificación, sensibilidad, sensibilidad analítica y rango de trabajo. Los resultados establecieron el desempeño satisfactorio de FAAS-FAES y MIP OES para cationes intercambiables. MIP OES es una alternativa eficaz a FAAS FAES, con amplio rango dinámico lineal, lo que resulta ventajoso en cuanto a las concentraciones en las que se encuentran estos cationes intercambiables en los suelos, evitando diluciones de muestra. La ventaja más notable de MIP OES son los bajos costes de funcionamiento, ya que no utiliza gases inflamables ni tóxicos. Debido a sus beneficios, MIP OES podría recomendarse como el principal método analítico para la determinación de cationes intercambiables. Más información sobre este texto de origenPara obtener más información sobre la traducción, se necesita el texto de origen Enviar comentarios Paneles laterales